aeskey.c File Reference

#include "aesopt.h"

Include dependency graph for aeskey.c:

Go to the source code of this file.

Defines

#define ke4(k, i)
#define kel4(k, i)
#define ke6(k, i)
#define kel6(k, i)
#define ke8(k, i)
#define kel8(k, i)


Define Documentation

#define ke4 ( k,
 ) 

Value:

{   k[4*(i)+4] = ss[0] ^= ls_box(ss[3],3) ^ t_use(r,c)[i]; k[4*(i)+5] = ss[1] ^= ss[0]; \
    k[4*(i)+6] = ss[2] ^= ss[1]; k[4*(i)+7] = ss[3] ^= ss[2]; \
}

Definition at line 63 of file aeskey.c.

#define ke6 ( k,
 ) 

Value:

{   k[6*(i)+ 6] = ss[0] ^= ls_box(ss[5],3) ^ t_use(r,c)[i]; k[6*(i)+ 7] = ss[1] ^= ss[0]; \
    k[6*(i)+ 8] = ss[2] ^= ss[1]; k[6*(i)+ 9] = ss[3] ^= ss[2]; \
    k[6*(i)+10] = ss[4] ^= ss[3]; k[6*(i)+11] = ss[5] ^= ss[4]; \
}

Definition at line 72 of file aeskey.c.

#define ke8 ( k,
 ) 

Value:

{   k[8*(i)+ 8] = ss[0] ^= ls_box(ss[7],3) ^ t_use(r,c)[i]; k[8*(i)+ 9] = ss[1] ^= ss[0]; \
    k[8*(i)+10] = ss[2] ^= ss[1]; k[8*(i)+11] = ss[3] ^= ss[2]; \
    k[8*(i)+12] = ss[4] ^= ls_box(ss[3],0); k[8*(i)+13] = ss[5] ^= ss[4]; \
    k[8*(i)+14] = ss[6] ^= ss[5]; k[8*(i)+15] = ss[7] ^= ss[6]; \
}

Definition at line 82 of file aeskey.c.

#define kel4 ( k,
 ) 

Value:

{   k[4*(i)+4] = ss[0] ^= ls_box(ss[3],3) ^ t_use(r,c)[i]; k[4*(i)+5] = ss[1] ^= ss[0]; \
    k[4*(i)+6] = ss[2] ^= ss[1]; k[4*(i)+7] = ss[3] ^= ss[2]; \
}

Definition at line 67 of file aeskey.c.

#define kel6 ( k,
 ) 

Value:

{   k[6*(i)+ 6] = ss[0] ^= ls_box(ss[5],3) ^ t_use(r,c)[i]; k[6*(i)+ 7] = ss[1] ^= ss[0]; \
    k[6*(i)+ 8] = ss[2] ^= ss[1]; k[6*(i)+ 9] = ss[3] ^= ss[2]; \
}

Definition at line 77 of file aeskey.c.

#define kel8 ( k,
 ) 

Value:

{   k[8*(i)+ 8] = ss[0] ^= ls_box(ss[7],3) ^ t_use(r,c)[i]; k[8*(i)+ 9] = ss[1] ^= ss[0]; \
    k[8*(i)+10] = ss[2] ^= ss[1]; k[8*(i)+11] = ss[3] ^= ss[2]; \
}

Definition at line 88 of file aeskey.c.


Generated on Wed Oct 28 17:00:48 2009 for Asterisk by  doxygen 1.5.6